Introdução e retomada de tópicos em entrevista televisiva - Douran, Carmen Lucia Milito (2014)
The purpose of this study is to analyze the linguistic-discursive procedures used by interlocutors in order to introduce and to take back the discursive topics in a television interview. In the attempt to clarify facts or bring insightful information, several procedures were used by the interviewer in order to get a better development of the proposed topics by the interviewee In turn, the interviewee interacted with the interviewer, sometimes accepting and developing the proposed topics, sometimes refusing some that could possibly put a positive self-image in vulnerability. Considered the topic, the conductive element of the event (since the dialogue means the topics and it is about the topics that are also chosen by the dialogue), the main objective was therefore to get evidence the collaborative contribution among the participants in shaping the topic board in view of the elements that are configured to delineate the social role that incorporate the interactants in the construction and consolidation of their public self-image. For the Corpus was selected an interview with the Governor of the State of São Paulo, Geraldo Alckmin showed by the program “De frente com Gabi”,transmitted on 11/30/2011 by the television station SBT (Brazilian Television System). In this program, which one, part of the planning conversational is local (concomitant with its execution), interaction strategies and arguments are used in order to monitor the discursive topic. The data, of empirical nature, were analyzed based on the fundamentals of Conversation Analysis supported by the "Principles of Cooperation" proposed by Grice (1982) and the procedures for the preservation of the face studied by Goffman (2011), proceeding to a description and qualitative interpretation.